Cracking more password hashes with patterns - Tatlı, Emin İslam (Institute of Electrical and Electronics Engineers, 2015)
It is a common mistake of application developers to store user passwords within databases as plaintext or only as their unsalted hash values. Many real-life successful hacking attempts that enabled attackers to get unauthorized access to sensitive database entries including user passwords have been experienced in the past. Seizing password hashes, attackers perform brute-force, dictionary, or rainbow-table attacks to reveal plaintext passwords from their hashes. Dictionary attacks are very fast for cracking hashes but their success rate is not sufficient. In this paper, we propose a novel method for improving dictionary attacks. Our method exploits several password patterns that are commonly preferred by users when trying to choose a complex and strong password. In order to analyze and show success rates of our developed method, we performed cracking tests on real-life leaked password hashes using both a traditional dictionary and our pattern-based dictionary. We observed that our pattern-based method is superior for cracking password hashes.
WOS: 000359984600009
Keywords: Password Security; Authentication; Data Security; Dictionary Attacks; Hash Cracking